1977
DOI: 10.1111/j.1744-6570.1977.tb02316.x
|View full text |Cite
|
Sign up to set email alerts
|

Black‐white Differences in Work Environment Perceptions and Job Satisfaction and Its Correlates

Abstract: Numerous studies have reported racial differences in intelligence, abilities, motivation, job satisfaction, and so forth. Relatively few of these studies, however, limited their comparisons to blacks and whites experiencing similar work conditions. The present effort compared black (n= 166) and white (n= 1,451) sailors assigned to the same shipboard divisions in order to investigate possible differences in perceived work conditions, satisfaction, need strength, and relationships among these variables. Also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 13 publications
(10 reference statements)
3
24
0
Order By: Relevance
“…Most analyses have found that among male enlistees, the perceptions of job satisfaction among blacks and whites are similar, unlike in civilian occupations (Fredland and Little 1983;Jones et al 1977;Wilson and Butler 1978). A more recent study, which included both Latinos and females, found that active duty black members are less satisfied than whites (Sanchez et al 2004).…”
Section: Job Satisfaction In the Militarymentioning
confidence: 99%
“…Most analyses have found that among male enlistees, the perceptions of job satisfaction among blacks and whites are similar, unlike in civilian occupations (Fredland and Little 1983;Jones et al 1977;Wilson and Butler 1978). A more recent study, which included both Latinos and females, found that active duty black members are less satisfied than whites (Sanchez et al 2004).…”
Section: Job Satisfaction In the Militarymentioning
confidence: 99%
“…This result parallels findings reported in studies of racial differences (Jones, James, Bruni, & Sells, 1977;Moch, 1980) that many apparent race-related differences diminish when adjusted for work group assignment, individual values, and other social variables. In the current study sex differences were not observed when men and women were placed in equivalent positions (i.e., medical males and medical females in this analysis).…”
Section: Job Category and Sex Differencessupporting
confidence: 68%
“…; : p:% = 18L-would be reduced. The results of recent studies (Jones, et al, 1977;Moch, 1980) concerning racial differences in work environment perceptions and job satisfaction attest to such a likelihood. These researchers concluded that many apparent race-related differences diminished or disappeared when adjusted for such variables as work gruup assignment, individual values, and other social variables.…”
Section: Summnarymentioning
confidence: 88%
“…Although inconclusive results have been found for several demographic characteristics including sex (Gruneberg, 1979;Weaver, 1980), income (Agho, Mueller, & Price, 1993;Glisson & Durick, 1988), education (Agho et al, 1993;Oldham & Hackman, 1981) other demographic variables have demonstrated more stable findings. Older age, for example, has been shown to be associated with greater job satisfaction (e.g., Agho et al, 1993;Biegen, 1993;Brush, Moch, & Pooyan, 1987), and African-American race generally has been associated with lower job satisfaction (Jones, James, Bruni, & Sells, 1977;Weaver, 1980). It has been suggested that the extent to which personal characteristics influence job satisfaction in the military is an important consideration (Fredland & Little, 1983), and that not enough studies of job satisfaction have controlled for the effects of demographics variables (Brush et al, 1987).…”
Section: Demographic Predictors Of Job Satisfactionmentioning
confidence: 99%